P233 A Case of CMV (Cancer Mimicking Virulence). (30th June 2016) - Boylan, Johnny; Greenhouse, Peter; Horner, Patrick
Abstract : Background/introduction: Generalised lymphadenopathy and fatigue have a broad differential diagnosis ranging from curable infections to lymphoma. Certain diagnoses can be delayed or missed altogether when patients do not present to sexual health clinics. Aim(s)/objectives: Highlight secondary syphilis as a cause of lymphadenopathy amongst non-sexual health colleagues. Expand syphilis testing beyond sexual health clinics, even in the absence of classical risk factors. Methods: Case report of secondary syphilis which was misdiagnosed despite numerous investigations in primary and secondary care. Results: A 23 year Caucasian lady was referred to lymphoma clinic by her GP with a three month history of lymphadenopathy and fatigue. She was diagnosed with a primary CMV infection and lost to follow up after her symptoms resolved. One year later she attempted to donate blood. Positive syphilis serology with a low RPR was detected on routine blood screening by the transfusion service. The patient was referred to Bristol Sexual Health Centre where sexual history taking revealed she had a bi sexual partner at the time of her illness who also tested positive for syphilis. An archived blood sample from the time of her illness revealed active syphilis infection with a high RPR. Discussion/conclusion: Secondary syphilis can mimic numerous illnesses. However syphilis testing remains uncommon outside of sexual health clinics for a variety of reasons. A change of culture is required to ensure medical professionals are prepared for routine sexual enquiry and consider syphilis as a potential cause for lymphadenopathy.